2017
DOI: 10.1016/j.juro.2017.02.2301
|View full text |Cite
|
Sign up to set email alerts
|

Mp69-05 Twitter Mentions and Academic Citations in Urology Literature

Abstract: INTRODUCTION AND OBJECTIVES: Clinical trials have suggested that pelvic floor rehab (PFR) can improve early urinary control following radical prostatectomy. However, the details surrounding its use in clinical practice and its contribution to cost and value are not well understood. In this context, we examined the use of PFR in a diverse statewide quality improvement collaborative, including patient characteristics, implementation patterns, and costs.METHODS: Using registry data from the Michigan Urological Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Despite the aforementioned limitations, for the first time in coloproctology the present study demonstrates that articles featured on Twitter are more likely to have higher citation counts than other articles. This is consistent with the results of previous, broader studies regarding social media and citation . Studies have further found that colorectal surgeons tend to be weakly engaged with social media and that, although the uptake of social media is steadily increasing, a large geographical variation still persists .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Despite the aforementioned limitations, for the first time in coloproctology the present study demonstrates that articles featured on Twitter are more likely to have higher citation counts than other articles. This is consistent with the results of previous, broader studies regarding social media and citation . Studies have further found that colorectal surgeons tend to be weakly engaged with social media and that, although the uptake of social media is steadily increasing, a large geographical variation still persists .…”
Section: Resultssupporting
confidence: 91%
“…Hayon et al . have proposed that one could estimate the ultimate academic impact of a paper by observing the number of Tweets and re‐Tweets of that paper on Twitter . To quantitatively assess the impacts of papers featured on Twitter, Cardona‐Grau et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations